The use of kinship terms in language learning: a perspective from language instructors / Sop Kum Yoke, Carolyn, Nor Haniza Hasan and Derwina Daud - Sop, Carolyn Kum Yoke; Hasan, Nor Haniza; Daud, Derwina (2011)
This study investigates the use of kinship terms by ESL learners under the framework of componential analysis. Componential analysis imposes binary aspects to meanings to language with semantic implications. Three respondents from specific cultural backgrounds, namely, Chinese, Indian and Malay were asked to fill in a table and to complete a tree diagram. They were also interviewed and specific questions related to kinship terms to help facilitate the study were developed. The findings showed that (i) the differences in kinship terms could influence acquisition in terms of semantic notions and (ii) cultural diversity influences language use. The implication to classroom learning is the knowledge of interference from the mother tongue when transferred to language teaching. Exploring this area of semantic notions and cultural diversity should also help in bridging the gap of understanding in language use and culture.